2022
DOI: 10.1038/s41598-022-18909-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal smoke exposure and congenital heart defects from a case–control study in China

Abstract: There is a gap in knowledge how maternal exposure to environmental tobacco smoke (ETS) is associated with offspring congenital heart defects (CHDs). In this case–control study, we collected data on 749 fetuses with CHDs and 880 fetuses without any congenital anomalies to examine the association of maternal ETS with fetal CHDs and the potentially moderating effect by maternal hazardous and noxious substances (HNS), periconceptional folate intake and paternal smoking. Maternal exposure to ETS in first trimester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Periconceptional cigarette smoking 21–24 1 month before conception through 3 months after conception is associated with an increased odds of ASD (OR, 1.7 [95% CI, 1.5–2.0]), truncus arteriosus (OR, 1.7 [95% CI, 1.0–2.7]), any septal defect (OR, 1.5 [95% CI, 1.3–1.7]), double-outlet right ventricle (OR, 1.3 [95% CI, 1.1–2.2]), perimembranous VSD (OR, 1.3, [95% CI, 1.0–1.4]), atrioventricular septal defect (OR, 1.3 [95% CI, 1.0–1.9]), right-sided obstructive lesion (OR, 1.2 [95% CI, 1.0–1.4]), and pulmonary valve stenosis (OR, 1.2 [95% CI, 1.0–1.4]). There was not a significant association between this exposure and truncus arteriosus (OR, 1.2 [95% CI, 0.7–2.1]) and Ebstein anomaly (OR, 1.1 [95% CI, 0.7–1.8]).…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…Periconceptional cigarette smoking 21–24 1 month before conception through 3 months after conception is associated with an increased odds of ASD (OR, 1.7 [95% CI, 1.5–2.0]), truncus arteriosus (OR, 1.7 [95% CI, 1.0–2.7]), any septal defect (OR, 1.5 [95% CI, 1.3–1.7]), double-outlet right ventricle (OR, 1.3 [95% CI, 1.1–2.2]), perimembranous VSD (OR, 1.3, [95% CI, 1.0–1.4]), atrioventricular septal defect (OR, 1.3 [95% CI, 1.0–1.9]), right-sided obstructive lesion (OR, 1.2 [95% CI, 1.0–1.4]), and pulmonary valve stenosis (OR, 1.2 [95% CI, 1.0–1.4]). There was not a significant association between this exposure and truncus arteriosus (OR, 1.2 [95% CI, 0.7–2.1]) and Ebstein anomaly (OR, 1.1 [95% CI, 0.7–1.8]).…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…Both Song et al [ 42 ] and Wang et al [ 41 ] reported an increased risk of CHD in offspring whose mothers were exposed to SHS during the three months before pregnancy. All three identified articles showed significant associations between maternal exposure to ETS and CHDs in their offspring [ 42 , 45 , 46 ] also found a dose–response gradient between the risk of CHDs and maternal exposure to ETS in first trimester of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…This widespread habit could impair the intrauterine environment and adversely affect the developing organs of offspring. 3 , 4 Previous studies have extensively documented the correlation between maternal smoking during pregnancy and low birth weight, 5 , 6 , 7 premature births, 8 congenital heart defects, 9 , 10 chronic obstructive pulmonary disease, 11 anxiety and depression, 12 and other disorders in offspring.…”
Section: Introductionmentioning
confidence: 99%